Evaluating Participant Outcomes in the Weather Monitoring Citizen Science Project “Delft Meet Regen” - Jordy Janssen; Marit Bogert; Margaret Gold; Sandra de Vries (Citizen Science: Theory and Practice)
Understanding the outcomes and impacts achieved in citizen science (CS) initiatives is essential for evaluating and enhancing participatory research practices. There is increasing attention paid in the literature to the broad range of benefits experienced by participants in CS initiatives. While existing frameworks provide structured guidance for the evaluation of participant outcomes, they might overlook nuanced participant experiences. This study explores outcomes reported by participants from the Delft Meet Regen (Delft Measures Rain, DMR) project, a CS initiative focused on environmental monitoring. Using semi-structured qualitative interviews to inductively collect participant outcomes, we applied a combination of the Individual Learning Outcomes (ILO) and Impact Domain (ID) frameworks to reflect on these outcomes with participants. Participants reported meaningful experiences such as a sense of contribution, increased awareness of rainfall patterns, and strengthened feelings of pre-existing environmental stewardship. These outcomes did not neatly align with predefined categories of the ILO and ID frameworks, and this illustrates the complexity of evaluating participant outcomes. Our findings highlight the value of integrating inductive qualitative methods within structured evaluations. By sharing these findings, we aim to support the continued development of comprehensive evaluation tools that fully capture the complex experiences of citizen scientists.